2013
DOI: 10.11648/j.sjcm.20130206.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Utilization of Insecticide Treated Nets among People Living with HIV/Aids in Bahir Dar City, Northwest Ethiopia

Abstract: Introduction: Malaria and HIV are among the two most important global health problems of this time. All HIV-positive persons (PLHAs) in the household were encouraged to sleep under insecticide treated nets (ITNs) at all times of year. However, the information on utilization and associated factors on these groups have been limited. Objective: the aim of the study was to assess utilization of ITN and associated factors among PLHA, who are members of the three PLHA associations in Bahir City Administration, north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
5
11
1
Order By: Relevance
“…Similar results have been found in other studies [21], [22]. Moreover other study reported those who have better income were 1.8 times more likely utilize ITN than have less income [23]. This might be people with low income concerns about the cost of ITNs and absence of a sustainable mechanism for the distribution of ITNS.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been found in other studies [21], [22]. Moreover other study reported those who have better income were 1.8 times more likely utilize ITN than have less income [23]. This might be people with low income concerns about the cost of ITNs and absence of a sustainable mechanism for the distribution of ITNS.…”
Section: Discussionsupporting
confidence: 88%
“…When inward our focus to our country, study on 606 students on AAU, one of the oldest and biggest university in Ethiopia, showed that more than half (52.4%) of the students prefer abstinence as top prevention measure (13,14,15) which was almost the same with this study result. Also study on WolaitaSodo University, one of newly built university in Southern Ethiopia, from the total 750 undergraduate students which the study incorporates 97.3% had good knowledge about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results have been obtained in some other African countries and also in Asian countries by Lin et al [ 24 ], Rhee et al in Mali [ 17 ] and Elsheikh in Sudan [ 18 ], who used health education as intervention. Also a slightly lower result was reported by Berie et al in Ethiopia, who found that the utilization of ITNs was 76.8 % [ 32 ], and a higher result was reported by Amoran, in Nigeria who found that the utilization of ITNs increased after health promotion message from 50.8 to 87.4 % (p < 0.001) [ 33 ], and also by Adebayo et al in Nigeria who found that the utilization of ITNs was 83.5 % [ 34 ].…”
Section: Discussionmentioning
confidence: 78%